1997
DOI: 10.1097/00005373-199704000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Selective Intestinal Decontamination in Multiple Trauma Patients

Abstract: We found no benefit of selective decontamination in trauma patients. Apparently, bacterial overgrowth in the intestinal tract is not the sole link between trauma, sepsis, and organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 32 publications
0
29
0
2
Order By: Relevance
“…Randomization was adequate in four studies (22,23,26,30), and blinding was used in six studies (22,23,(25)(26)(27)(28). Nine RCTs included adults (21)(22)(23)(24)(25)(26)(27)(28)(29) and one included pediatric patients (30). Selected populations were liver transplant recipients (21) and cardiac surgery patients (22,30).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomization was adequate in four studies (22,23,26,30), and blinding was used in six studies (22,23,(25)(26)(27)(28). Nine RCTs included adults (21)(22)(23)(24)(25)(26)(27)(28)(29) and one included pediatric patients (30). Selected populations were liver transplant recipients (21) and cardiac surgery patients (22,30).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies did not use the full protocol of SDD, and in three (22,23,25) only the gut was decontaminated. MODS was the end point in seven studies (21,23,(25)(26)(27)(28)30); however, in the other three studies (22,24,29) data on MODS were also reported. Two RCTs (22,29) did not report any definition of MODS; the remaining studies used different definitions, derived from Knaus (31), Cerra (32), Goris (33), Marshall (10), miscellaneous (31,33,34), and Wilkinson (for pediatric population) (35).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Gastinne et al (1992) and Wiener et al (1995) demonstrated that oropharyngeal and intestinal decontamination had no impact on the incidence of VAP, although colonisation with MDR bacteria was endemic in these sites, which may explain their results. This was also the case in the ICUs, where authors of several studies (Hammond et al 1992;Ferrer et al 1994;Lingnau et al 1997) concluded that SDD (oropharyngeal and intestinal decontamination, with systemic antimicrobial prophylaxis), versus systemic antimicrobial prophylaxis alone, had little positive effect on pneumonia rates, although, in this situation, it may be argued that systemic prophylaxis alone had a protective effect against the development of VAP, and not the topical application of antibiotics. However, SDD should not be used in an ICU where there is endemic colonisation with drug-resistant bacteria.…”
Section: Selective Decontamination Of the Digestive Tract (Sdd)mentioning
confidence: 95%
“…Importantly, however, the studies that do not support a benefit were carried out in ICUs with high levels of antibiotic resistance [5,6,7,8,9,10]. Although the evident impact of SDD on reducing incidence rates of ventilator-associated pneumonia (VAP) appears to be inversely related to the methodological quality of the SDD study, the benefits remain significant in "high-quality" studies [11].…”
Section: Effects Of Sdd On Icu-acquired Infectionsmentioning
confidence: 99%